If it bleeds : new fiction - King, Stephen, 1947- (New York : Simon & Schuster, 2020)
"The four never-before-published novellas in this collection represent horror master King using the weird and uncanny to riff on mortality, the price of creativity, and the unpredictable consequences of material attachments. A teenager discovers that a dead friend's cell phone, which was buried with the body, still communicates from beyond the grave in 'Mr. Harrigan's Phone,' which reads like a Twilight Zone episode infused with an EC Comics vibe. In the profoundly moving 'The Life of Chuck,' a series of apocalyptic incidents bear out one character's claim that 'when a man or a woman dies, a whole world falls to ruin.' 'Rat' sees a frustrated writer strike a Faustian bargain to complete his novel, and in the title story, private investigator Holly Gibney, the recurring heroine of King's Bill Hodges trilogy and The Outsider, faces off against a ghoulish television newscaster who vampirically feeds off the anguish he provokes in his audience by covering horrific tragedies"--Publishers Weekly.
Mr. Harrigan's phone -- The life of Chuck -- If it bleeds -- Rat.
Four novellas.
Maine author.
Keywords: Short stories, American; Horror tales, American; Good and evil -- Fiction; Horror fiction; Novellas